E-Learning in Higher Education: Transforming Teaching and Learning Strategies in the Digital Era - Andi Widya (Generasi Sains Indonesia, 2025)
This study aims to analyze the influence of e-learning adoption on teaching strategies and learning interactions in higher education. The study used a quantitative approach with a survey of 200 students to measure factors such as perceived usefulness, perceived ease of use, teacher presence, peer interaction, and cognitive engagement. The results showed that perceived usefulness and teacher presence were the main factors determining the quality of learning interactions, while perceived ease of use played a supporting role, and interaction between students and cognitive engagement had a smaller influence. These findings confirm that the success of e-learning depends not only on technology, but also on effective pedagogical strategies and the active involvement of lecturers. This study provides implications for universities, lecturers, and policymakers in optimizing the implementation of e-learning as a pedagogical transformation in the digital era.